2009
DOI: 10.1590/s1984-46702009000400018
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of Imparfinis schubarti (Siluriformes: Heptapteridae) from the Piumhi drainage, a diverted river in Minas Gerais State, Brazil

Abstract: Specimens of Imparfinis schubarti (Gomes, 1956) collected in the Piumhi river drainage, state of Minas Gerais, Brazil, were studied cytogenetically. The river was diverted from the Rio Grande Basin into the São Francisco basin in the early 1960s. All individuals presented 2n = 58 chromosomes, including 18 metacentric, 34 submetacentric and six subtelocentric chromosomes. A secondary constriction was observed in the interstitial region of the long arm of the largest chromosome pair, coinciding with the NOR. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 16 publications
1
18
1
Order By: Relevance
“…In contrast, Kantek et al (2009) observed this site only in a big submetacentric chromosome pair of the constriction that also showed synteny with the 18S rDNA site in I. schubarti from Pihumi River/MG/ Brazil. However, the two populations of I. schubarti, in this study, showed the 5S rDNA site on a small metacentric chromosome (pair 10), which does not show synteny with the 18S rDNA site, as was observed with the double FISH technique.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In contrast, Kantek et al (2009) observed this site only in a big submetacentric chromosome pair of the constriction that also showed synteny with the 18S rDNA site in I. schubarti from Pihumi River/MG/ Brazil. However, the two populations of I. schubarti, in this study, showed the 5S rDNA site on a small metacentric chromosome (pair 10), which does not show synteny with the 18S rDNA site, as was observed with the double FISH technique.…”
Section: Discussionmentioning
confidence: 79%
“…However, there is variation regarding the chromosome type and presence of such sequences either on the short or long arm, even within the same species (Kantek et al 2009;Garcia and AlmeidaToledo 2010a, b;Martinez et al 2011). The Heptapteridae family also shows variation in chromosome number bearing this site, and only one pair of chromosomes (Kantek et al 2009;Garcia and Almeida-Toledo 2010a;Martinez et al 2011) or two pairs of chromosome carriers are found (Garcia and Almeida-Toledo 2010a, b;Ferreira et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…schubarti (Kantek et al, 2009), were similar in terms of the Ag-NORs. The NORs observed on the long arm of different types of chromosome in this genus can be explained by rearrangements, such as inversions, deletions, and duplications (Borba et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…The values of 2n = 58 chromosomes and NF = 116, which were found in the present study, are the most common in the genus, being also observed in I. mirini (Vissotto et al, 1997), I. piperatus (Vissotto et al, 2001), I. aff. schubarti (Stolf et al, 2004), and I. schubarti (Kantek et al, 2009). Differences in karyotype formula and 2n have been found between different species and populations of Imparfinis; however, the high frequency of species with 2n = 58 chromosomes, which is considered not only ancestral for the Heptapteridae but also for the Siluriformes as a whole, indicate that non-Robertsonian chromosomal rearrangements were the most frequent rearrangements made during the karyotypic evolution of the genus.…”
Section: Discussionmentioning
confidence: 99%